2013
DOI: 10.1177/1053825913498372
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Developmental Adventure on the Self-Esteem of College Students

Abstract: This study examines the effects of outdoor developmental adventure programming (ODA) on college students’ self-esteem. Although some previous studies have shown that outdoor adventure programming has positive effects on self-esteem, others did not find any effect. A quasi-experimental study was conducted over 5 months, which included two pretests and two posttests to address some limitations of previous studies. A total of 84 participants completed the Questionnaire d’estime de soi hiérarchique, a questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Post hoc independent t-tests revealed that there was a significant difference between boys and girls selfesteem pre-wilderness expedition (t(122)= 2.96; P<0.01); but not post-expedition. Boys' self-esteem was higher than that of girls pre-expedition, but this difference did not exist post-expedition (Table 2002; Ewert and McAvoy, 2000;Asfeldt and Hvengaard, 2014;Paquette et al, 2014). Existing literature also suggests that the effects of wilderness expedition's increase, and are maintained over time (Hattie et al, 1997;Asfeldt and Hvenegaard, 2014); indicating that improvements in self-esteem experienced as a result of a wilderness expedition could have long lasting effects.…”
Section: Self-esteemmentioning
confidence: 99%
See 2 more Smart Citations
“…Post hoc independent t-tests revealed that there was a significant difference between boys and girls selfesteem pre-wilderness expedition (t(122)= 2.96; P<0.01); but not post-expedition. Boys' self-esteem was higher than that of girls pre-expedition, but this difference did not exist post-expedition (Table 2002; Ewert and McAvoy, 2000;Asfeldt and Hvengaard, 2014;Paquette et al, 2014). Existing literature also suggests that the effects of wilderness expedition's increase, and are maintained over time (Hattie et al, 1997;Asfeldt and Hvenegaard, 2014); indicating that improvements in self-esteem experienced as a result of a wilderness expedition could have long lasting effects.…”
Section: Self-esteemmentioning
confidence: 99%
“…The restorative properties of the wilderness foster personal, social and emotional growth (Davis-Berman and Berman 1994a, 1994b, 2008Russell 2001Russell , 2006Norton & Watt, 2014), including significant changes in self-esteem, self-efficacy, selfimage, self-control, self-confidence, self-empowerment and decision making (Cason and Gillis, 1993;Hans, 2000;Hattie, Marsh, Neill and Richards, 1997;Russell, 2006b;Hoag et al, 2013;Asfeldt and Hvenegaard, 2014;Paquette et al, 2014). Wilderness settings are also used as part of formal therapy in adolescents, improving psychological functioning and reducing distress related to interpersonal and mental health challenges (Berman and Davis-Berman, 2013;Norton et al, 2013;Hoag et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most researchers defined creativity with the "product" of creativity. Ewert & Sibthorp (2014) proposed 4P of creativity to integrate the research area of creativity and considered to study creativity from the directions of 1.creative product, 2.creative person, 3.creative process, and 4.creative place (Paquette et al, 2014). regarded creativity as the most precious treasure in human brains and the foundation of future and divided it into sensitivity, fluency, flexibility, originality, and elaboration.…”
Section: Creativitymentioning
confidence: 99%
“…Richards et al (2013) studied the effects of the exploratory education activity program on junior high school students in gifted classes; researched the effect of exploratory education activity on the promotion of elementary school gifted students; Sibthorp & Morgan (2011) studied the teaching effect of leadership ability on elementary school gifted students; and, Paquette et al (2014) researched teenagers' experience in participating in exploratory activity. The above studies showed the notably positive effects of exploratory education activity on the cultivation of leadership ability.…”
Section: Research Hypothesismentioning
confidence: 99%